Cross-linked single-walled carbon nanotube aerogel electrodes via reductive coupling chemistry. Issue 15 (3rd March 2016) - De Marco, Martina; Markoulidis, Foivos; Menzel, Robert; Bawaked, Salem M.; Mokhtar, Mohamed; Al-Thabaiti, Shaeel A.; Basahel, Sulaiman N.; Shaffer, Milo S. P.
Abstract : Spontaneously-dissolved, negatively-charged SWCNTs were cross-linked using p -diiodobenzene to produce ultralight, high surface area cryogels with high conductivity, suitable for supercapacitors application. Abstract : Single-walled carbon nanotube (SWCNT) anions can be cross-linked by a dielectrophile to form covalent, carbon-bonded organogels. Freeze-drying produces cryogels with low density (2.3 mg cm −3 ), high surface area (766 m 2 g −1 ), and high conductivity (9.4 S m −1 ), showing promise as supercapacitor electrodes. Counterion concentration controls debundling, grafting ratio, as well as all the resulting properties.